Meta Analysis of the Randomized Controlled Trial of Acupuncture for Ankylosing Spondylitis - Ping LI; Yinjie WANG; Jigang TIAN (康复学报)
Objective:To evaluate the clinical effect of acupuncture in the treatment of ankylosing spondylitis and provide evidence-based medical evidence for clinical practice.Methods:Randomized controlled trials(RCT)about acupuncture(trial group)compared with medicines(control group)in the treatment of ankylosing spondylitis were collected from five major databases at home and abroad(CNKI, VIP database, Chinese Biomedical Database, Wanfang database, PubMed)from January 2000 to February 2018.Two independent reviewers screened the articles, extracted data and assessed the risk of bias. The evaluation of the quality was performed using Cochrane Risk of Bias evaluation criterion and Modified Jadad Scales; besides the data was analyzed by using RevMan 5.3 software. Bi-categorized variables were represented by risk rate(RR)or odds ratio(OR)and its 95%confidence interval(CI)and continuous variables were represented by weighted mean difference(MD)and its 95%CI.Results:Finally, 11 clinical randomized controlled trials were included. All of them were Chinese literatures. A total of 767 participants involving 395 patients were included in the trial group and 372 patients in the control group. According to meta analysis, the total effective rate of acupuncture in the treatment of ankylosing spondylitis was higher than that of the control group [RR=1.26, 95%CI(1.17, 1.35), P< 0.000 01], and the difference was statistically significant(P< 0.05).Thoracic distance [MD=0.41, 95%CI(0.26, 0.56), P< 0.000 01], finger distance [MD=-4.97, 95%CI(-9.06, -0.89), P=0.02], erythrocyte sedimentation rate [MD=-8.46, 95%CI(-14.00, -2.92), P=0.003], C-reactive protein [MD=-23.20, 95%CI(-40.68, -5.73), P=0.009] of the trial group were significantly improved better than those of the control group, and the differences were statistically significant(P< 0.05). However, there were no significant differences in improving the disease activity index of ankylosing spondylitis score [MD=-5.36, 95%CI(-12.99, -2.26), P=0.17], the functional index of ankylosing spondylitis score [MD=-4.25, 95%CI(-8.81, 0.31), P=0.07] and the adverse reaction rate [OR=0.12, 95%CI(0.01, 1.64), P=0.11] between the two groups(P> 0.05). The sensitivity analysis of the total effective rate was carried out by removing one of them one by one and then merging the effect quantity analysis. Meta analysis results showed that the difference of total effective rate had statistical significance(P< 0.05)after eliminating one of the documents in turn. The merging effect was determined by RR and the obtained RR was relatively stable. Sensitivity analysis showed that the research was homogeneous and the results of the meta analysis were stable.Conclusion:Acupuncture has certain advantages in the treatment of ankylosing spondylitis, and it is helpful to improve the activity of thoracic spine, the activity of lumbar spine and the inflammatory markers(erythrocyte sedimentation rate, C-reactive protein)in patients with ankylosing spondylitis as a result. So acupuncture in the treatment of ankylosing spondylitis is worthy of clinical use. However, this study is based on literature data; the quality and quantity of literature maybe have significant influence on the final results. Therefore, it is necessary to conduct more high-quality and large-sample studies, so as to provide a more reliable evidence-based basis for the treatment of ankylosing spondylitis by acupuncture.